The Application of Problem Based Learning Improves the Learning Outcomes of Electric Motor Installation for Students of SMKN 1 Kulisusu - Rasyid, Muhammad; Algaus, Icong; Waode, Hamdi (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This classroom action research aims to improve the learning process by applying a problem based learning model to improve learning outcomes for the Electric Motor Installation Protection System class XI TITL students of State Vocational High School 1 Kulisusu This study uses two stages of the cycle Cycle I students achieved learning outcomes of 45 7 incomplete and 54 8 completed with an average score of 68 34 Cycle II students achieved learning outcomes of 11 42 incomplete and 88 57 completed with an average value of 82 51 Applying this learning improves student outcomes in the second cycle stage namely the achievement results of 88 57 of the total 35 students with an average value of 82 51 Thus a problem based learning model can improve student learning outcomes in class XI TITL State Vocational High School 1 Kulisusu < p>